Leukemia - Guenova, Margarita; Balatzenko, Gueorgui (IntechOpen, 2013)
Leukemias are a group of heterogeneous neoplastic disorders, that differ significantly in terms of morhological, immunophenotypic, cytogenetic and molecular features of malignant cells. These specific features reflect the differences in the spectrum of underlying biological alterations involved in malignant transformation, and/or variations in the level of hematopoietic stem cells hierarchy where the transforming events occur. The continuous and rather extensive influx of new information regarding the pathogenesis and treatment of leukemias requires a frequent updating of this topic. The primary objective of this book is to provide the specialists involved in the diagnosis and management of acute and chronic leukemias with a comprehensive and concise information on some important theoretical and practical issues of the biology and clinical presentation, the diagnosis, treatment and follow up of patients with leukemias.